FINANCING ECONOMIC DEVELOPMENT IN LIDYA - elhassia, m (Dirasat in Economics and Business, 1984)
In his article we try to discover how Leer mic development is being financcd in Libyan economy following the tradi lonal classification of finance into inter.al and external finance. Using a newly coastracted flow-c! Cand account the Libyan economy in 1517 Logether with information about the retudes of national income saving ud investment for the period 106 1010 WC lyve kuluded that: As a result of the non-existence of de financial instruments and institutiens otser then commercial banks to gether with the tendency of these banks to keep a high percentage of their assets in a liquid form and the persistence of the public of keeping a high percentage of their money holdings in terms of currency, the lending-borrowing activity through financial Intermediation in the Libyan economy has become very limited and consequently the concept of external finance of cconomic develop ment, which in turn has resulted in a high dependence of economic development on internal finance instead.